"Lets talk about you …": Opening space for local experience, action and learning in disaster risk reduction. Issue 5 (11th July 2016) - Gibson, Terry; Wisner, Ben
Abstract : Purpose: The purpose of this paper is to report on the creation of innovative methods for engaging in conversations about everyday risk. Design/methodology/approach: A range of methods from conventional survey research to open-ended, semi-structured conversations and focus groups were used in the series of studies that serve as the subject of this meta-study. The meta-study uses participant observation, key informant interviews and project reports to narrate and evaluate the evolution of Frontline as an action planning, monitoring, advocacy and research tool. Findings: The Views from the Frontline (VFL) methods began as the bottom-up mirror of a top-down monitoring approach used by the United Nations (Hyogo Framework for Action Monitor). Limitations of such bottom up monitoring led to creation of guidelines for formalising local knowledge resulting from actions – Action at the Frontline (AFL) and, later, Frontline, a flexible tool for eliciting experiences of everyday risk. The earlier VFL monitoring approach had shared outsiders' assumptions about the nature of the "problem" and limited the degree to which local residents could express their own experiences and priorities. Originality/value: Extensive use of this suite of methods has shown that civil society organisations are fully capable of conducting credible research when properly supported and motivated. Use of these methods has so far provided strong support for policy advocacy at the global scale, has had moderate success in liaison with national policy makers and slow but promising results as a learning/action tool at the local scale. Frontline has as yet untapped potential as a resource for academic research.